Pengaruh Transformational Leadership dan Transactional Leadership Terhadap Employee Performance Pada PT Glostar Indonesia 1 Cikembar Sukabumi - David Saktiadi Girsang; Bambang Somantri (Winter Journal: IMWI Student Research Journal, 2020)
This study aims to determine: (1) the effect of transformational leadership style on employee performance, (2) the effect of transactional leadership on employee performance, and (3) the effect of transformational leadership and transactional leadership simultaneously on employee performance. The subjects of this study were all employees of PT. Glostar Indonesia 1 located at Cikembar Sukabumi. The number of respondents in this study were 100 people. The method of collecting data through a survey using a questionnaire. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results showed that (1) transformational leadership style has effect on employee performance. (2) transactional leadership style has effect on employee performance. 3) simultaneously transformational leadership style and transactional leadership style have effect on employee performance. Further research is needed by this company so that employees will able to produce high performance.